Visual Culture in Social Media: A Study on the Influence of Instagram on Aesthetics and Youth Culture Trends - Fauzi Eka Putra; Pepy Afrilian (Asian Journal of Media and Culture, 2025)
This study examines the influence of visual aesthetics on Instagram in shaping social identity and user behavior, with a focus on how the visual standards on this platform affect how individuals express themselves. Using a literature review method, this research gathers and analyzes various relevant sources, including academic articles, journals, and previous research reports, to explore the impact of visual aesthetics on Instagram users. The main findings of this study show that the visual aesthetics on Instagram, which often create idealized representations of the self, play a significant role in the formation of individual social identity. Users, especially younger ones, are frequently influenced by the beauty standards and lifestyles promoted by influencers, reinforcing the tendency to compare themselves with more "perfect" images. This can negatively impact mental health, such as increasing anxiety and body dissatisfaction. However, this research also finds that the platform offers space for more inclusive self-expression, particularly for marginalized groups, such as the LGBTQ+ community and specific ethnic groups, who use Instagram to showcase their cultural identities. This study highlights the importance of awareness of the influence of visual aesthetics on social media in shaping self-perception and social relationships, as well as the need for a more sensitive approach to diversity in the use of digital platforms